If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + x = 3(x + -7) + 6 Reorder the terms: 5 + x = 3(-7 + x) + 6 5 + x = (-7 * 3 + x * 3) + 6 5 + x = (-21 + 3x) + 6 Reorder the terms: 5 + x = -21 + 6 + 3x Combine like terms: -21 + 6 = -15 5 + x = -15 + 3x Solving 5 + x = -15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5 + x + -3x = -15 + 3x + -3x Combine like terms: x + -3x = -2x 5 + -2x = -15 + 3x + -3x Combine like terms: 3x + -3x = 0 5 + -2x = -15 + 0 5 + -2x = -15 Add '-5' to each side of the equation. 5 + -5 + -2x = -15 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = -15 + -5 -2x = -15 + -5 Combine like terms: -15 + -5 = -20 -2x = -20 Divide each side by '-2'. x = 10 Simplifying x = 10
| 5x+15y=55 | | (4x+1)(6x+3)= | | 5-2x=3+x-4-3x | | 2x+11=-5-2x | | 5q^2-2q=4q^2-4q+15 | | 3(p^2-18p+81)=81 | | -4(x+5)=10 | | 24+8=-2x+10x | | 4(x+7)=23 | | 3x+8-10x=14 | | M^2+8M=3 | | 1150/20.70%= | | 110/70= | | 35=3.50x+7 | | B^2=175 | | 172=12x-5+82 | | Y=3.50(4)+7 | | 8+3-12+6= | | Y=3.50(9)+9 | | 9x^2-12x=-1 | | 3.50x+7=9 | | 2+5n=27 | | 6x+3x=9+12x | | 3z+4=10 | | 6x+3y+2z=44 | | 5(f-2)=5 | | 8(s-7)=-84 | | -(c-4)=2 | | 2(t+4)=0 | | 3(t+1)=-1+2(t-3) | | 12-7=56-21x | | 5(4s+4)=220 |